A perovskite-type cage compound as a temperature-triggered dielectric switchable material. Issue 40 (14th September 2016) - Qian, Kun; Shao, Feng; Yan, Zhihong; Pang, Jie; Chen, Xiaodong; Yang, Changxin
Abstract : The perovskite-type cage compound [C3 H6 NH2 ]2 [KCo III (CN)6 ] shows a temperature-triggered dielectric switch. The switchable properties are derived from an order–disorder phase transition of a system, by changing the motions of the polar azetidine cation guests. Abstract : The perovskite-type cage compound [C3 H6 NH2 ]2 [KCo III (CN)6 ] shows a temperature-triggered dielectric switch. The switchable properties around 199 K were revealed by crystal structure studies between low and high dielectric states. They are derived from an order–disorder phase transition of a system, by changing the motions of the polar azetidine cation guests.